The Effect of Working Hours of The Ship's Main Engine on The Temperature of The Fresh Water Cylinder Cooling System In Diesel Engines - lilik budiyanto; Natalino Fonseca Da Silva Guterres; Aprilina (Universitas Wahid Hasyim, 2025)
Main propulsion engines on commercial ships are generally of the diesel type, necessitating precise and stable thermal conditions for efficient operation. To ensure this thermal stability, the engine's cylinders are equipped with a dedicated freshwater cooling system. The primary objective of this study was to ascertain the correlation between fluctuating operating hours and temperature variations within the engine's cylinder cooling system. The resulting data will inform the establishment of a robust maintenance protocol to preserve the main engine's peak performance. The research was executed over a 48-hour period onboard an inter-island container vessel traversing the Makassar Strait, where the ambient seawater temperature was consistently measured at . The findings revealed that the cylinder outlet temperature of the freshwater coolant maintained a satisfactory stable level during the initial period (00:00 to 16:00). Subsequently, a temperature increase was observed from 16:00 to 20:00, followed by a decline in engine temperature between 20:00 and 24:00. A particular finding was the persistently elevated temperature recorded in Cylinder No. 7. Consequently, immediate and thorough inspection and maintenance are recommended for Cylinder No. 7 to mitigate the risk of severe or progressive damage.